Synchronous pulmonary carcinoid tumour and non-Hodgkin's lymphoma: report of two cases. Issue 6 (June 1989) - Juettner, F M; Fellbaum, C; Popper, H; Lehnert, M; Neubauer, M; Wagner, W; Becker, H
Abstract : Two cases of synchronous pulmonary carcinoid tumour and non-Hodgkin's lymphoma are described.